Preventive Strategies Against Cytomegalovirus and Incidence of α‐Herpesvirus Infections in Solid Organ Transplant Recipients: A Nationwide Cohort Study. Issue 7 (2nd February 2017) - Martin‐Gandul, C.; Stampf, S.; Héquet, D.; Mueller, N. J.; Cusini, A.; van Delden, C.; Khanna, N.; Boggian, K.; Hirzel, C.; Soccal, P.; Hirsch, H. H.; Pascual, M.; et al.
Abstract : We assessed the impact of antiviral preventive strategies on the incidence of herpes simplex virus (HSV) and varicella‐zoster virus (VZV) infections in a nationwide cohort of transplant recipients. Risk factors for the development of HSV or VZV infection were assessed by Cox proportional hazards regression. We included 2781 patients (56% kidney, 20% liver, 10% lung, 7.3% heart, 6.7% others). Overall, 1264 (45%) patients received antiviral prophylaxis (ganciclovir or valganciclovir, n = 1145; acyclovir or valacyclovir, n = 138). Incidence of HSV and VZV infections was 28.9 and 12.1 cases, respectively, per 1000 person‐years. Incidence of HSV and VZV infections at 1 year after transplant was 4.6% (95% confidence interval [CI] 3.5–5.8) in patients receiving antiviral prophylaxis versus 12.3% (95% CI 10.7–14) in patients without prophylaxis; this was observed particularly for HSV infections (3% [95% CI 2.2–4] versus 9.8% [95% CI 8.4–11.4], respectively). A lower rate of HSV and VZV infections was also seen in donor or recipient cytomegalovirus‐positive patients receiving ganciclovir or valganciclovir prophylaxis compared with a preemptive approach. Female sex (hazard ratio [HR] 1.663, p = 0.001), HSV seropositivity (HR 5.198, p < 0.001), previous episodes of rejection (HR 1.95, p = 0.004), and use of a preemptive approach (HR 2.841, p = 0.017) were significantly associated with a higher risk of HSV infection. Although HSV and VZV infections were common after transplantation, antiviral prophylaxis significantly reduced symptomatic HSV infections. Abstract : In this national cohort of solid organ transplant recipients, patients receiving antiviral prophylaxis either with (val)ganciclovir or (val)acyclovir have a lower incidence of herpes simplex virus infections compared to patients managed with a preemptive approach for cytomegalovirus infection or not receiving antiherpes prophylaxis.